Synthesis of ZnO nanoparticles by co-precipitation technique and characterize the structural and optical properties of these nanoparticles. Issue 1 (1st September 2022) - Ghosh, Soumyadev; Ghosh, Abhishek; Pramanik, Subhamay; Kuiri, Probodh K.; Sen, Rupam; Neogi, Swarup Kumar
Abstract : The present work demonstrates synthesis and study of physical properties of chemically synthesized ZnO nanoparticles by co-precipitation technique. Detailed synthesis procedure had been described in the experimental section. Chemically synthesized ZnO samples were annealed at 300°C and 500°C. These samples have been characterized by doing X-Ray diffraction (XRD), photoluminescence (PL) and Raman spectroscopy. XRD patterns indicate wurzite structure of these samples. SEM pictures shows growth of grain size with annealing temperature treatment. The lattice parameters (a & c) of ZnO samples are showing increasing tendency with annealing treatment. PL spectra with excitation wavelength : λex =330 nm exhibit a broad and asymmetric UV band centred around 386 nm (~ 3.212 eV) and 390 nm (~ 3.179 eV) respectively for the 300°C and 500°C annealed samples. Broad UV emission band indicating that, it has defect related origin. The Raman spectra of these samples indicate that intensity of Raman peaks improves with annealing at the higher temperature. Possibly high temperature annealing (500°C) brings modification into the micro-structure. The micro-structure and optical properties of these synthesized samples are compared with that of pure ZnO powder samples. Finally correlation between structural and optical properties has been made based on the analysis of experimental data.